2019
DOI: 10.1124/dmd.119.087742
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cryopreserved Hepatocytes as Part of an Integrated Strategy to Characterize In Vivo Clearance for Peptide-Antibody Conjugate Inhibitors of Nav1.7 in Preclinical Species

Abstract: The identification of nonopioid alternatives to treat chronic pain has received a great deal of interest in recent years. Recently, the engineering of a series of Nav1.7 inhibitory peptide-antibody conjugates has been reported, and herein, the preclinical efforts to identify novel approaches to characterize the pharmacokinetic properties of the peptide conjugates are described. A cryopreserved plated mouse hepatocyte assay was designed to measure the depletion of the peptide-antibody conjugates from the media,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…Although it has been recognized for many years that ADC design can profoundly impact pharmacokinetics, antitumor activity, and tolerability, the ADC field has lacked in vitro assays to predict in vivo pharmacokinetics . This lack of early discovery ADME tools has put researchers in the ADC field at a disadvantage relative to their colleagues who develop small molecules, in light of the long history of in vitro systems to predict the intrinsic metabolic clearance of these drugs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been recognized for many years that ADC design can profoundly impact pharmacokinetics, antitumor activity, and tolerability, the ADC field has lacked in vitro assays to predict in vivo pharmacokinetics . This lack of early discovery ADME tools has put researchers in the ADC field at a disadvantage relative to their colleagues who develop small molecules, in light of the long history of in vitro systems to predict the intrinsic metabolic clearance of these drugs .…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been recognized for many years that ADC design can profoundly impact pharmacokinetics, antitumor activity, and tolerability, the ADC field has lacked in vitro assays to predict in vivo pharmacokinetics. 25 This lack of early discovery ADME tools has put researchers in the ADC field at a disadvantage relative to their colleagues who develop small molecules, in light of the long history of in vitro systems to predict the intrinsic metabolic clearance of these drugs. 3 Previously, we reported that the apparent hydrophobicity of an ADC, as judged by its retention time from a hydrophobic interaction chromatography (HIC) column, correlated reasonably well with its plasma clearance in a rat pharmacokinetic study.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In vitro assays that can provide information on the in vivo pharmacokinetic behavior of a molecule prior to conducting in vivo studies are crucial to informing the design of new modalities and can increase the speed at which new modalities reach clinical trials (Xu and Vugmeyster, 2012;Pearson and Rock, 2015). One such assay described in this issue is a novel in vitro assay by Foti et al that informs how new chemical entities such as peptide-antibody conjugates will behave in vivo and provides a basis on which to prioritize molecules for in vivo studies (Foti et al, 2019). Advancements in the sensitivities of bioanalytical techniques have also enhanced the ability to measure drug at the site of action (Foti et al, 2015).…”
Section: Biodistribution and Pharmacokinetic Considerations Of New Momentioning
confidence: 99%